(untitled) (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
This study employs bibliometric analysis to examine the development of research on digital innovation in batik entrepreneurship, with a specific focus on Giriloyo MSMEs in Yogyakarta, Indonesia. Using bibliometric analysis, the study systematically maps the evolution, key contributors, and thematic structures of scholarly publications on digital innovation, batik, and cultural entrepreneurship between 2015 and 2025. A total of 366 peer-reviewed journal articles were extracted from the CrossRef database, screened for relevance, and analyzed using Publish or Perish and VOSviewer software. The analysis reveals five main thematic clusters linking digital innovation to sustainability, cultural entrepreneurship, MSME performance, and creative value creation The results demonstrate a significant growth in scholarly attention from descriptive studies of cultural industries to more integrative discussions connecting digital transformation, resilience, and community empowerment. The Giriloyo Batik Center exemplifies how digital transformation supports cultural preservation, market expansion, and the resilience of local MSMEs. By identifying key trends, influential authors, and research gaps, this study contributes evidence-based insights for scholars and policymakers to advance sustainable digital entrepreneurship in traditional industries.